2008
DOI: 10.1007/s11661-008-9538-x
|View full text |Cite
|
Sign up to set email alerts
|

Interface Effects on the Quasi-Static and Impact Toughness of Discontinuously Reinforced Aluminum Laminates

Abstract: Trilayer laminates consisting of two layers of aluminum alloy 7093 surrounding one layer of 7093/SiC/15 p were produced via two roll-bonding techniques as well as by adhesive bonding. The effects of systematic changes in interface characteristics (i.e., weak bond via roll bonding with a thin ductile interlayer material, stronger bond via roll bonding without a thin ductile interlayer, and strongest bond via adhesive bonding with a semibrittle material) on the subsequent laminate toughness was studied. The frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 42 publications
1
8
1
Order By: Relevance
“…They also reported that the maximum toughness was achieved in laminate having the intermediate interfacial strength accompanied with proper delamination. This result contradicted with that of Osman et al. (2008), which illustrated that the least interfacial adhesion resulted in maximum damage tolerance in three-layer Al7093/Al7093-15 vol.% SiC p /Al7093 laminates.…”
Section: Introductioncontrasting
confidence: 62%
See 3 more Smart Citations
“…They also reported that the maximum toughness was achieved in laminate having the intermediate interfacial strength accompanied with proper delamination. This result contradicted with that of Osman et al. (2008), which illustrated that the least interfacial adhesion resulted in maximum damage tolerance in three-layer Al7093/Al7093-15 vol.% SiC p /Al7093 laminates.…”
Section: Introductioncontrasting
confidence: 62%
“…Also, according to ASTM E399, the length of notch was equal to the thickness of samples. Primary notch was induced by wire cut due to the difficulty and possibility of having different crack lengths in dissimilar layers associated with producing a planar crack front during fatigue precracking in laminates in divider orientation (Osman et al., 2008).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The occurrence of these fracture mechanisms is responsible for the enhanced toughness of the post-rolling tempered and T6-treated ADL11 composite laminate. Previous investigations [29][30][31] have proposed different models to calculate the contribution of crack-bridging mechanism to the toughness in ceramic/metal laminates, being the metal layer constrained between ceramic layers. In the present study, additional extrinsic fracture-toughness mechanisms are present, such as delamination and crack renucleation in the ductile-aluminum layers, making very difficult the calculation of each toughening mechanism separately.…”
Section: B Mechanical Propertiesmentioning
confidence: 99%